A review of involution and its psychological interpretation - Kang, Lei; Jin, Yeyao (Filozofia Publiczna i Edukacja Demokratyczna, 2020)
In recent years, the concept of involution has been widely spread, and more and more articles begin to use the concept with its extended meanings to discuss social problems in China. Howev-er, there is little discussion on the evolving meanings of involution, which makes the use of the concept quite arbitrary. In the early stage of the development of involution, it was a concept based on econom-ic theory and the tendency of the generalization of the concept calls for more systemic discussion across academic disciplines. In order to take a new perspective to understand employee performance, espe-cially some deviant or withdrawal behaviors, this paper analyzes the specific meaning of the concept and the possible psychological fac-tors behind it. After the theoretical discussion of the concept, this paper also tries to seek solutions to effective motivation at workplace.